B-LYMPHOPLASMACYTIC LYMPHOMA WITH WALDENSTRÖM’S MACROGLOBULINEMIA VARIANT - Nikolenko, D.Ye.; Stetsuk, Ye.V.; Zadvornova, A.P. (World of Medicine and Biology, 2025)
A hematological malignant disease of human lymphoid tissue in the form of a rare Waldenström disease with a long asymptomatic course and short-term clinical course usually ends fatally for an elderly patient. Clinical verification of the disease is based on a monoclonal IgM diagnosis and bone marrow biopsy results. The purpose of the study was to deepen knowledge of the clinical course and pathomorphological diagnosis of lymphoid organ tumors of B-cell origin, specifically Waldenström macroglobulinemia, a variant of non-Hodgkin lymphoma. The research methods were a review of the professional scientific literature on the pathology of B-cell lymphomas and a retrospective clinical and anatomical analysis of a fatal case of Waldenström’s disease in an elderly patient with a short clinical course and concomitant diseases of a compensated nature in the form of general vascular atherosclerosis and hypertension. As a result of the literature analysis, data were obtained on the molecular basis of the mechanism of formation of tumors of the immune system of B-lymphocyte origin, which are associated with the MYD88 gene with the L265P mutation; CXCR4 with oncogenic properties and changes in certain “signaling proteins” CD79B, MYD88 and others. They transmit an activating signal to cell proliferation genes through receptors on their surface, which are activated upon interaction with specific antigens, interleukins from macrophages, T-lymphocyte helpers, chemokines from bone marrow stromal cells, and lymph nodes. The mutual potentiating effect stimulates proliferation and uncontrolled activity of the tumor clone of lymphocytes. As a result of the analysis of the autopsy protocol and clinical and anatomical epicrisis of the case from the clinic, the course of Waldenström macroglobulinemia disease was clarified, and the possibilities of additional methods of verification of this pathology were explored.